Interrelationships between writing anxiety dimensions and writing goal orientation among Iraqi EFL undergraduates - Sabti, Ahmed Abdulateef; Md Rashid, Sabariah; Hummadi, Ali Salman (Faculty of Education, Eskisehir Osmangazi University, 2019)
This study aimed to examine the relationships between facilitating writing anxiety (FWA), debilitating writing anxiety (DWA), mastery-approach goal (MAG), performance-approach goal (APPG) and performance-avoidance goal (AVOG). In total, 300 Iraqi undergraduate students participated in the study. A quantitative approach was applied in particular correlational design. Two questionnaires were utilized for data collection: The Second Language Writing Anxiety Inventory (SLWAI) and Achievement Goal Questionnaire (AGQ). The results of the study indicated that some students showed a high rate of debilitating anxiety, which led them to pursue performance-avoidance goal. Yet, the two factors of performance- avoidance goal and debilitating writing anxiety were negatively associated with the set of the three factors: mastery-approach goal, performance-approach goal and facilitating writing anxiety. Conversely, there were positive relationships between mastery-approach goal, performance-approach goal and facilitating writing anxiety. In the light of these findings, this study proposes that EFL learners need to consider the affective factors of debilitating anxiety and performance avoidance goal that are likely to undermine their confidence and motivation which may lead them to a maladaptive behavior.